2015
DOI: 10.4067/s0034-98872015000400007
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores de fragilidad en adultos mayores del sistema público de salud de la ciudad de Antofagasta

Abstract: Rates of frailty among older people ascribed to chilean primary care clinics (Rev Med Chile 2015; 143: 459-466)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 14 publications
0
2
0
28
Order By: Relevance
“…It sets diagnostic categories called self-functioning without risk, self-functioning with risk, and risk of dependency 19 . This instrument has been validated by the behavior of indicators of fragility according to their diagnostic categories 20 .…”
Section: Methodsmentioning
confidence: 99%
“…It sets diagnostic categories called self-functioning without risk, self-functioning with risk, and risk of dependency 19 . This instrument has been validated by the behavior of indicators of fragility according to their diagnostic categories 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In a study developed in the interior of Paraíba, 71.9% of the sample did not have depressive symptoms and, when present, they were associated with female, divorced, absence of religion and chronic illness; similar to a study carried out in Chile, whose use of the Mental State Mini Exam showed cognitive decline in only 4.5% of the sample (15) .…”
Section: Discussionmentioning
confidence: 59%
“…Diseño: observacional, descriptivo, prospectivo, de corte transversal, multicéntrico Población de estudio: varones y mujeres ≥60 años asistidos por las USF de Yuquyty, Costa Fleytas y Caacupemí (Areguá, Paraguay) en 2019. Criterios de inclusión: capacidad de comunicarse con el personal de salud (10) Criterios de exclusión: discapacidad física, deterioro cognitivo severo, postración Fragilidad: presencia de 3 ó más de los 5 ítems de los criterios de Fried Instrumentos de medición: Cuestionario de datos demográficos y clínicos. Escala de fragilidad de Fried : 1.…”
Section: Materials Y Métodosunclassified
“…Todas (7)(8)(9) requieren estrategias preventivas, diagnósticas y terapéuticas diferentes . La fragilidad no es el (10) estado previo a la discapacidad sino la predisposición a desarrollarla . La fragilidad tiene ciertas características: es multidimensional, crónica, progresiva, tiene impacto negativo en el paciente y en los sistemas de salud.…”
Section: Introductionunclassified
See 1 more Smart Citation